Highly scalable and flexible on-chip all-silicon mode filter using backward mode conversion gratings - Zhang, Lei; Guo, Zhenzhao; Gu, Xiaofei; Chen, Yufei; San, Xingyuan; Xiao, Jinbiao; Wu, Shengbao (Optics express, 2022)
Mode filters are fundamental elements in a mode-division multiplexing (MDM) system for reducing modal cross-talk or realizing modal routing. However, the previously reported silicon mode filters can only filter one specific mode at a time and multiple modes filtering usually needs a cascade of several filters, which is adverse to highly integrated MDM systems. Here, we propose a unique concept to realize compact, scalable and flexible mode filters based on backward mode conversion gratings elaborately embedded in a multimode waveguide. Our proposed method is highly scalable for realizing a higher-order-mode-pass or band-mode-pass filter of any order and capable of flexibly filtering one or multiple modes simultaneously. We have demonstrated the concept through the design of four filters for different order of mode(s) and one mode demultiplexer based on such a filter, and the measurement of two fabricated 11μm length filters (TE1-pass/TE2-pass) show that an excellent performance of insertion loss <1.0dB/1.5dB and extinction ratio >29dB/28.5dB is achieved over a bandwidth of 51.2nm/48.3nm, which are competitive with the state-of-the-art.